Cladribine to treat disease exacerbation after fingolimod discontinuation in progressive multiple sclerosis. Issue 7 (17th May 2017) - Alvarez‐Gonzalez, Cesar; Adams, Ashok; Mathews, Joela; Turner, Benjamin P.; Giovannoni, Gavin; Baker, David; Schmierer, Klaus
Abstract: Rebound disease following cessation of disease modifying treatment (DMT) has been reported in people with both relapsing and progressive multiple sclerosis (pwRMS, pwPMS) questioning strict separation between these two phenotypes. While licensed DMT is available for pwRMS to counter rebound disease, no such option exists for pwPMS. We report on a pwPMS who developed rebound disease, with 45 Gadolinium‐enhancing lesions on T1 weighted MRI brain, within 6 months after fingolimod 0.5 mg/day was stopped. Treatment with a short course of subcutaneous cladribine 60 mg led to effective suppression of inflammatory activity and partial recovery with no short‐term safety issues or adverse events.